2-Cyano-2-indolylpropanoic acid as a chiral derivatizing agent for the absolute configuration assignment of secondary alcohols and primary amines by 1H NMR and VCD. Issue 6 (15th June 2017) - Bautista-Hernández, Claudia I.; Trejo-Carbajal, Nayely; Zúñiga-Estrada, Erick A.; Aristeo-Dominguez, Alberto; Meléndez-Rodríguez, Myriam; Suárez-Castillo, Oscar R.; Sánchez-Zavala, Maricruz; Cruz-Borbolla, Julián; Morales-Ríos, Martha S.; Joseph-Nathan, Pedro
Graphical abstract: Absolute configuration assignment by 1 H NMR and vibrational circular dichroism exciton coupling. Abstract: A convenient approach for the absolute configuration assignment of secondary alcohols in the (8 R, 1′ R, 2′ S, 5′ R )-15, 25, (8 S, 1′ R, 2′ S, 5′ R )-15, 25, (8 R, 1′ R )-21 –24, and (8 S, 1′ R )-21 –24 ester series, and of primary amines in the (8 R, 1′ R )-32 –37 and (8 S, 1′ R )-32 –37 amide series, by means of 1 H NMR and VCD spectroscopy, using 2-cyano-2-indolylpropanoic acid as a chiral derivatizing agent is presented. DFT calculations were carried out to demonstrate the anisotropic effect of the indole skeleton on the chiral alcohol or the amine fragment. Vibrational circular dichroism (VCD) measurements of the above series indicated a VCD bisignated couplet resulting from the interaction of the ester carbonyl group and the CN group. The absolute configuration assignments were further tested by X-ray diffraction analysis. Abstract : (−)-(1 R, 2 S, 5 R )-2-Isopropyl-5-methylcyclohexyl ( R )-2-cyano-2-(1 H -indol-3-yl)propanoate: C22 H28 N2 O2 Ee >98% (by 1 H NMR) [ α ] D 20  = −36.0 ( c 1.0, CHCl3 ) Source of chirality: (−)-(1 R, 2 S, 5 R )-Menthol Absolute configuration: (8 R, 1′ R, 2′ S, 5′ R )-15 Abstract : (−)-(1 R, 2 S, 5 R )-2-Isopropyl-5-methylcyclohexyl ( S )-2-cyano-2-(1 H -indol-3-yl)propanoate: C22 H28 N2 O2 Ee >98% (by 1 H NMR) [ α ] D 20  = −90.8 ( c 1.0, CHCl3 ) Source of chirality: (−)-(1 R, 2 S, 5 R )-Menthol Absolute configuration: (8 S, 1′ R, 2′ S, 5′ R )-15 Abstract : (+)-(1 S, 2 R, 5 S )-2-Isopropyl-5-methylcyclohexyl ( R )-2-cyano-2-(1 H -indol-3-yl)propanoate: C22 H28 N2 O2 Ee >98% (by 1 H NMR) [ α ] D 20  = +91.5 ( c 1.0, CHCl3 ) Source of chirality: (+)-(1 S, 2 R, 5 S )-Menthol Absolute configuration: (8 R, 1′ S, 2′ R, 5′ S )-15 Abstract : (+)-(1 S, 2 R, 5 S )-2-Isopropyl-5-methylcyclohexyl ( S )-2-cyano-2-(1 H -indol-3-yl)propanoate: C22 H28 N2 O2 Ee >98% (by 1 H NMR) [ α ] D 20  = +36.5 ( c 1.0, CHCl3 ) Source of chirality: (+)-(1 S, 2 R, 5 S )-Menthol Absolute configuration: (8 S, 1′ S, 2′ R, 5′ S )-15 Abstract : (+)-(1 R, 2 S, 5 R )-5-Methyl-2-(prop-1-en-2-yl)cyclohexyl ( R )-2-cyano-2-(1 H -indol-3-yl)propanoate: C22 H26 N2 O2 Ee >98% (by 1 H NMR) [ α ] D 20  = +3.0 ( c 1.0, CHCl3 ) Source of chirality: (−)-(1 R, 2 S, 5 R )-isopulegol Absolute configuration: (8 R, 1′ R, 2′ S, 5′ R )-25 Abstract : (−)-(1 R, 2 S, 5 R )-5-Methyl-2-(prop-1-en-2-yl)cyclohexyl ( S )-2-cyano-2-(1 H -indol-3-yl)propanoate: C22 H26 N2 O2 Ee >98% (by 1 H NMR) [ α ] D 20  = −10.0 ( c 1.0, CHCl3 ) Source of chirality: (−)-(1 R, 2 S, 5 R )-isopulegol Absolute configuration: (8 S, 1′ R, 2′ S, 5′ R )-25 Abstract : (+)-( R )-2-Cyano-2-(1 H -indol-3-yl)propanoic acid: C12 H10 N2 O2 Ee >98% (by 1 H NMR) [ α ] D 20  = +58.5 ( c 1.0, EtOH) Source of chirality: (−)-(1 R, 2 S, 5 R )-Menthol Absolute configuration: ( R )-14 Abstract : (−)-( S )-2-Cyano-2-(1 H -indol-3-yl)propanoic acid: C12 H10 N2 O2 Ee >98% (by 1 H NMR) [ α ] D 20  = −58.0 ( c 1.0, EtOH) Source of chirality: (−)-(1 R, 2 S, 5 R )-Menthol Absolute configuration: ( S )-14 Abstract : (+)-( R )- sec -Butyl ( R )-2-cyano-2-(1 H -indol-3-yl)propanoate: C16 H18 N2 O2 Ee >98% (by 1 H NMR) [ α ] D 20  = +12.0 ( c 1.0, CHCl3 ) Source of chirality: (−)-( R )-2-butanol Absolute configuration: (8 R, 1′ R )-21 Abstract : (−)-( R )- sec -Butyl ( S )-2-cyano-2-(1 H -indol-3-yl)propanoate: C16 H18 N2 O2 Ee >98% (by 1 H NMR) [ α ] D 20  = −42.5 ( c 1.0, CHCl3 ) Source of chirality: (−)-( R )-2-butanol Absolute configuration: (8 S, 1′ R )-21 Abstract : (+)-( S )- sec -Butyl ( R )-2-cyano-2-(1 H -indol-3-yl)propanoate: C16 H18 N2 O2 Ee >98% (by 1 H NMR) [ α ] D 20  = +41.0 ( c 1.0, CHCl3 ) Source of chirality: (+)-( S )-2-butanol Absolute configuration: (8 R, 1′ S )-21 Abstract : (−)-( S )- sec -butyl ( S )-2-cyano-2-(1 H -indol-3-yl)propanoate: C16 H18 N2 O2 Ee >98% (by 1 H NMR) [ α ] D 20  = −11.5 ( c 1.0, CHCl3 ) Source of chirality: (+)-( S )-2-butanol Absolute configuration: (8 S, 1′ S )-21 Abstract : (+)-( R )-1-Phenylethyl ( R )-2-cyano-2-(1 H -indol-3-yl)propanoate: C20 H18 N2 O2 Ee >98% (by 1 H NMR) [ α ] D 20  = +11.8 ( c 1.0, CHCl3 ) Source of chirality: (+)-( R )-1-phenylethanol Absolute configuration: (8 R, 1′ R )-22 Abstract : (+)-( R )-1-Phenylethyl ( S )-2-cyano-2-(1 H -indol-3-yl)propanoate: C20 H18 N2 O2 Ee >98% (by 1 H NMR) [ α ] D 20  = +2.5 ( c 1.0, CHCl3 ) Source of chirality: (+)-( R )-1-phenylethanol Absolute configuration: (8 S, 1′ R )-22 Abstract : (+)-( R )-Oct-1-yn-3-yl ( R )-2-cyano-2-(1 H -indol-3-yl)propanoate: C20 H22 N2 O2 Ee >98% (by 1 H NMR) [ α ] D 20  = +54.5 ( c 1.0, CHCl3 ) Source of chirality: (+)-( R )-1-octyn-3-ol Absolute configuration: (8 R, 1′ R )-23 Abstract : (+)-( R )-Oct-1-yn-3-yl ( S) -2-cyano-2-(1 H -indol-3-yl)propanoate: C20 H22 N2 O2 Ee >98% (by 1 H NMR) [ α ] D 20  = +9.8 ( c 1.0, CHCl3 ) Source of chirality: (+)-( R )-1-octyn-3-ol Absolute configuration: (8 S, 1′ R )-23 Abstract : (+)-( R )-3-Chloro-1-phenylpropyl ( R )-2-cyano-2-(1 H -indol-3-yl)propanoate: C21 H19 Cl1 N2 O2 Ee >98% (by 1 H NMR) [ α ] D 20  = +10.2 ( c 1.0, CHCl3 ) Source of chirality: (+)-( R )-3-chloro-1-phenyl-1-propanol Absolute configuration: (8 R, 1′ R )-24 Abstract : (+)-( R )-3-Chloro-1-phenylpropyl ( S )-2-cyano-2-(1 H -indol-3-yl)propanoate: C21 H19 Cl1 N2 O2 Ee >98% (by 1 H NMR) [ α ] D 20  = +20.0 ( c 1.0, CHCl3 ) Source of chirality: (+)-( R )-3-chloro-1-phenyl-1-propanol Absolute configuration: (8 S, 1′ R )-24 Abstract : (+)-( R )-2-Cyano-2-(1 H -indol-3-yl)- N -(( R )-1-phenylethyl)propanamide: C20 H19 N3 O1 Ee >98% (by 1 H NMR) [ α ] D 20  = +14.0 ( c 1.0, CHCl3 ) Source of chirality: (+)-( R )-α-methylbenzylamine Absolute configuration: (8 R, 1′ R )-32 Abstract : (+)-( S )-2-Cyano-2-(1 H -indol-3-yl)- N -(( R )-1-phenylethyl)propanamide: C20 H19 N3 O1 Ee >98% (by 1 H NMR) [ α ] D 20  = −27.0 ( c 1.0, CHCl3 ) Source of chirality: (+)-( R )-α-methylbenzylamine Absolute configuration: (8 S, 1′ R )-32 Abstract : (+)-( R )- N -(( R )- sec -butyl)-2-cyano-2-(1 H -indol-3-yl)propanamide: C16 H19 N3 O1 Ee >98% (by 1 H NMR) [ α ] D 20  = +26.8 ( c 1.0, EtOH) Source of chirality: (−)-( R )- sec -butylamine Absolute configuration: (8 R, 1′ R )-33 Abstract : (−)-( S )- N -(( R )- sec -butyl)-2-cyano-2-(1 H -indol-3-yl)propanamide: C16 H19 N3 O1 Ee >98% (by 1 H NMR) [ α ] D 20  = −71.3 ( c 1.0, EtOH) Source of chirality: (−)-( R )- sec -butylamine Absolute configuration: (8 S, 1′ R )-33 Abstract : (−)-( R )-2-Cyano-2-(1 H -indol-3-yl)- N -(( R )-1-(naphthalen-1-yl)ethyl)propanamide: C24 H21 N3 O1 Ee >98% (by 1 H NMR) [ α ] D 20  = −44.5 ( c 1.0, CHCl3 ) Source of chirality: (+)-( R )-1-(1-naphthyl)ethylamine Absolute configuration: (8 R, 1′ R )-34 Abstract : (−)-( S )-2-Cyano-2-(1 H -indol-3-yl)- N -(( R )-1-(naphthalen-1-yl)ethyl)propanamide: C24 H21 N3 O1 Ee >98% (by 1 H NMR) [ α ] D 20  = −98.5 ( c 1.0, CHCl3 ) Source of chirality: (+)-( R )-1-(1-naphthyl)ethylamine Absolute configuration: (8 S, 1′ R )-34 Abstract : (+)-( R )-2-Cyano- N -(( R )-1-cyclohexylethyl)-2-(1 H -indol-3-yl)propanamide: C20 H25 N3 O1 Ee >98% (by 1 H NMR) [ α ] D 20  = +5.0 ( c 1.0, EtOH) Source of chirality: (−)-( R )-1-cyclohexylethylamine Absolute configuration: (8 R, 1′ R )-35 Abstract : (−)-( S )-2-Cyano- N -(( R )-1-cyclohexylethyl)-2-(1 H -indol-3-yl)propanamide: C20 H25 N3 O1 Ee >98% (by 1 H NMR) [ α ] D 20  = −74.0 ( c 1.0, EtOH) Source of chirality: (−)-( R )-1-cyclohexylethylamine Absolute configuration: (8 S, 1′ R )-35 Abstract : (+)-( R )-2-Cyano- N -((1 R, 2 R )-2-hydroxycyclohexyl)-2-(1 H -indol-3-yl)propanamide: C18 H21 N3 O2 Ee >98% (by 1 H NMR) [ α ] D 20  = +11.3 ( c 1.0, EtOH) Source of chirality: (1 R, 2 R )-2-aminociclohexanol Absolute configuration: (8 R, 1′ R )-36 Abstract : (−)-( S )-2-Cyano- N -((1 R, 2 R )-2-hydroxycyclohexyl)-2-(1 H -indol-3-yl)propanamide: C18 H21 N3 O2 Ee >98% (by 1 H NMR) [ α ] D 20  = −37.5 ( c 1.0, EtOH) Source of chirality: (1 R, 2 R )-2-aminociclohexanol Absolute configuration: (8 S, 1′ R )-36 Abstract : (−)-( R )-2-Cyano- N -(( R )-1-hydroxy-3-phenylpropan-2-yl)-2-(1 H -indol-3-yl)propanamide: C21 H21 N3 O2 Ee >98% (by 1 H NMR) [ α ] D 20  = +42.5 ( c 1.0, CHCl3 ) Source of chirality: (+)-( R )-2-amino-3-phenyl-1-propanol Absolute configuration: (8 R, 1′ R )-37 Abstract : (+)-( S )-2-Cyano- N -(( R )-1-hydroxy-3-phenylpropan-2-yl)-2-(1 H -indol-3-yl)propanamide: C21 H21 N3 O2 Ee >98% (by 1 H NMR) [ α ] D 20  = +5.5 ( c 1.0, CHCl3 ) Source of chirality: (+)-( R )-2-amino-3-phenyl-1-propanol Absolute configuration: (8 S, 1′ R )-37